Kastamonu Gazetesi (1882-1920) - Boyraz, Ekrem Zahid (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
Bu kitap, Kastamonu Gazetesi’nin (1882-1920) tarihini ve yayın öyküsünü ele almaktadır. Kitap, Osmanlı Devleti’nde basının durumunu ve ilk basım faaliyetlerini incelerken, özellikle Kastamonu’da basın faaliyetlerine odaklanmaktadır. Osmanlı’da yabancı ve Türkçe basının durumu detaylı bir şekilde ele alınmaktadır. Kastamonu’da ise gazeteler ve dergiler üzerinde durulmaktadır.Kitabın birinci bölümünde, Kastamonu Gazetesi’nin kuruluş amacı ve yayın öyküsü anlatılmaktadır. Osmanlı’da vilayet gazeteciliği ve gazetenin kuruluş süreci detaylı bir şekilde ele alınmaktadır. Gazetenin teknik tanıtımı da yapılmaktadır, sayfa, sütun ve ebadı gibi teknik detaylar açıklanmaktadır. Ayrıca gazetenin mizanpajı, ücreti, reklam ve ilan politikaları da incelenmektedir. Kitap, fotoğraf ve eklerin kullanımı hakkında da bilgi vermektedir. Bu kitap, Kastamonu Gazetesi’nin tarihini ve yayın öyküsünü detaylı bir şekilde ele alarak, okuyuculara Osmanlı basını ve Kastamonu’da basın faaliyetleri hakkında kapsamlı bir bilgi sunmaktadır. This book examines the history and publishing story of Kastamonu Newspaper (1882-1920). While exploring the state of the press in the Ottoman Empire and its initial publishing activities, the book specifically focuses on press activities in Kastamonu. It provides a detailed analysis of the state of foreign and Turkish-language press in the Ottoman Empire. In Kastamonu, the book delves into newspapers and magazines. The first chapter of the book narrates the purpose of the establishment and publishing story of Kastamonu Newspaper. It thoroughly discusses provincial journalism in the Ottoman Empire and the process of newspaper establishment. The technical aspects of the newspaper, such as page layout, columns, and size, are also described. Additionally, the book examines the newspaper’s typography, fees, advertising, and announcement policies. It also provides information on the use of photographs and supplements.By extensively exploring the history and publishing story of Kastamonu Newspaper, this book offers readers comprehensive knowledge about the Ottoman press and press activities in Kastamonu.